Developing Assessment in Indonesian EFL Speaking Classroom - Widiastuti, Oktavia (IALLTEACH (Issues In Applied Linguistics & Language Teaching), 2025)
Recently, considerable debate has emerged regarding the assessment of students’ speaking performance, particularly due to the influence of cultural and subjective factors that shape lecturers’ approaches to constructing speaking assessments. These ongoing discussions highlight the need for heightened awareness among educators about the complexities involved in evaluating oral proficiency. The primary aim of this paper is to propose a method for designing speaking assessments that are specifically tailored to the Indonesian higher education context. In doing so, the paper emphasizes the importance of adopting the criteria for effective assessment as outlined by (Brown & Abeywickrama, 2020). According to these scholars, an effective speaking assessment should be grounded in clearly defined criteria, involve tasks that are both appropriate and maximally productive, and utilize practical as well as reliable scoring procedures. Based on these principles, this paper recommends that lecturers develop speaking assessments that are not only methodologically sound but also contextually relevant and responsive to the unique needs of their students. By doing so, lecturers can ensure that their assessment practices are both fair and meaningful within the Indonesian university setting. The implementation of the proposed assessment model enables lecturers to conduct speaking evaluations that are fair, objective, and tailored to the Indonesian EFL context. This approach not only enhances the validity and reliability of speaking assessments but also supports students’ communicative competence and improves the overall quality of English language instruction at the university level.